Dexmedetomidine: Current Role in Anesthesia and Intensive Care - Afonso, Joana (2012)
Background and objectives: To update and review the application of dexmedetomidine in anesthesia and intensive care. This study is a comprehensive review of clinical uses, pharmacology, pharmacokinetics, mechanism of action and adverse effects of dexmedetomidine. Content: The effective use of sedative-hypnotic agents and analgesics is an integral part of comfort and safety of patients. Dexmedetomidine is a potent and highly selective α-2 adrenoceptor agonist with sympatholytic, sedative, amnestic, and analgesic properties, which has been described as a useful and safe adjunct in many clinical applications. It provides a unique “conscious sedation”, analgesia, without respiratory depression. The current reviewed uses include sedation at Intensive Care Unit – ICU (both adult and pediatric), emergency department, regional and general anesthesia, neurosurgery, sedation for pediatric procedures, awake fiber-optic intubation, cardiac surgery and bariatric surgery. Conclusions: Dexmedetomidine offers a unique ability of providing both sedation and analgesia without respiratory depression. It is a new agent with a wide safety margin, excellent sedative capacity and moderate analgesic properties. Although its wide use is currently in patients of surgical and non-surgical intensive care units, dexmedetomidine seems to have promising future applications in neuroprotection, cardioprotection and renoprotection. More detailed studies are required to define its role as sedative in critical, neurosurgical and pediatric patients, as anesthesia adjunct and sedative during procedures.